Strategi Public Relations Berbasis Digital untuk Promosi Museum Perkebunan Indonesia - Dama Kania Harahap; Elfiyanti Ritonga (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study explores the digital public relations strategy implemented by the Museum of Indonesian Plantation (Musperin) in building institutional image and expanding audience engagement in the digital communication era. Adopting a qualitative approach with a case study method, data were collected through direct observation and semi-structured interviews with museum management. The findings reveal that Musperin utilizes social media not merely for promotion, but also as an educational and participatory two-way communication platform. The strategy is analyzed using five digital PR elements proposed by Phillips & Young: transparency, porosity, the internet as an agent and content richness. Moreover, Musperin integrates Islamic communication values such as qaulan sadidan (truthful speech), fathanah (wisdom), and qaulan baligha (impactful delivery) in conveying its messages. These principles ensure that the institution communicates with honesty, intelligence, and clarity. The study concludes that a digital PR strategy that is adaptive, value-driven, and participatory is effective in enhancing institutional credibility and fostering audience trust, particularly among digital-native generations. The findings also suggest that such strategies can be applied to other thematic museums as a model for strengthening institutional presence and public engagement through creative, ethical, and interactive digital platforms.